Protective effects of vitamin C and selenium supplementation on methomyl-induced tissue oxidative stress in adult rats. (January 2015) - Djeffal, Assia; Messarah, Mahfoud; Boumendjel, Amel; Kadeche, Lilia; Feki, Abdelfattah El
Methomyl (MET) is used worldwide in agriculture and health programs. Besides its advantages in the agriculture, it causes several toxic effects. The objective of this study was to examine the potential ability of vitamin C and/or selenium (Se), to alleviate the oxidative damage parameters, against MET-induced changes in blood biochemical markers and oxidative damage in liver and kidney of male Wistar rats. The animals were randomized into five groups of eight each: group I served as control rats; group II received MET (8 mg/kg body weight (BW)) in drinking water; group III received both MET and vitamin C (200 mg/kg BW; by intraperitoneal injection); group IV received both MET and Se (0.6 mg/100 g BW). Animals of group V were treated with MET, vitamin C and Se. A significant increase in the levels of hepatic markers enzymes (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and lactate dehydrogenase) was determined. Furthermore, renal markers such as urea and creatinine were increased in MET-treated rats. Additionally, serum cholesterol and triglycerides were significantly enhanced. Exposure of rats to MET caused significant increase in malondialdehyde levels, thus causing a drastic alteration in antioxidant defense system, particularly in the activities of catalase and glutathione- S -transferase and glutathione peroxidase. However, simultaneous supplementation with vitamin C and Se restored these parameters partially. In conclusion, the results of the current study revealed that MET-induced toxicity caused perturbations of some biochemical parameters, lipid peroxidation and alterations in the antioxidant enzymes in liver and kidney homogenates. Administration of vitamin C and Se exhibited protective effect by inhibiting MET-induced toxicity in liver and kidney.